Secular Spirituality and the Foundations of Education Classroom - Don Hufford (The Advocate, 2015)
Every institution of higher education serves in some measure as a community of imagination in which every professor is potentially a spiritual guide and every syllabus a confession of faith (Parks, p. 159). In a somewhat radically-inspired foundations of education classroom, I seek to stimulate thinking, and questioning a little philosophical wondering and wandering - when I toss-out the statement that "teaching is a spiritual journey – as is life itself.”